Informed Leadership through Assessment Workshops - Frederick Burrack; Chris Urban (Academic Chairpersons Conference Proceedings, 2018)
The first half of this workshop is focused on the responsibility of academic leaders to develop a culture of assessment. Participants will leave this workshop with strategies to guide faculty in defining learning outcomes, aligning course and program learning expectations, designing meaningful assessments, and using assessment data to inform program decisions. The second half of this workshop will demonstrate advanced assessment processes that empower faculty through automated data collection, interactive visualization, and enriched analysis. Program leaders will learn how to use advanced assessment processes to exceed institutional and accreditation expectations, and reimagine strategic goals.
Keywords: Assessment Leadership Analysis Informed Kansas